2008
DOI: 10.1044/1059-0889(2008/07-0045)
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Modal Interactions of Auditory and Somatic Inputs in the Brainstem and Midbrain and Their Imbalance in Tinnitus and Deafness

Abstract: Purpose This review outlines the anatomical and functional bases of somatosensory influences on auditory processing in the normal brainstem and midbrain. Thereafter, it explores how interactions between the auditory and somatosensory system are modified through deafness and their impact on tinnitus is discussed. Methods literature-review, tract-tracing, immunohistochemistry, in vivo electrophysiological recordings Results Somatosensory input originates in the dorsal root ganglia (DRG) and trigeminal gangli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(96 citation statements)
references
References 103 publications
1
91
0
4
Order By: Relevance
“…Dehmel et al 31 , also found similar results. Further, Cook-Huvnh 32 has indicated that there is an increasing prevalence of hypertension and diabetes mellitus in the adults and geriatrics.…”
Section: Other Risk Factorssupporting
confidence: 76%
“…Dehmel et al 31 , also found similar results. Further, Cook-Huvnh 32 has indicated that there is an increasing prevalence of hypertension and diabetes mellitus in the adults and geriatrics.…”
Section: Other Risk Factorssupporting
confidence: 76%
“…Therefore, it is possible that deafness-induced changes in somatosensory processing at the sub-cortical level could account for the massive redistribution of that information manifested as cortical cross-modal reorganization. Furthermore, given that the auditory pathways are highly crossed in their projections from brainstem to cortex, deafness-induced somatic inputs to the first station of this relay (40,46) could generate a large proportion of bilateral receptive fields at higher levels, as was observed.…”
Section: Discussionmentioning
confidence: 85%
“…It is well established in hearing animals that somatosensory afferents converge on auditory neurons at various sub-cortical levels within the auditory system, including the cochlear nucleus and inferior colliculus (40,41). In hearing animals, dorsal cochlear nucleus neurons respond to somatosensory stimulation of the pinna, vibrissa, neck, and forelimb (42), and neurons in the external nucleus of the inferior colliculus respond to displacement of hairs and light touch on the bilateral or contralateral body surface, with no apparent somatotopic organization (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…Since the excitatory CN-commissural pathway resembles that of non-auditory (somatosensory) projection neurons (Dehmel et al 2008;Haenggeli et al 2005;Wright and Ryugo 1996;Zhou et al 2007;Zhou and Shore 2004), it is likely to have a similar modulatory function as suggested for these non-auditory projections and may be associated with DCN synaptic plasticity under normal-hearing conditions (Tzounopoulos et al 2004;Young et al 1995;Zhou et al 2007). …”
Section: Discussionmentioning
confidence: 98%